Advancing electronic health record vendor usability maturity: Progress and next steps. (31st January 2021) - Hettinger, Aaron Z; Melnick, Edward R; Ratwani, Raj M
Abstract: Despite basic federal requirements promoting a user-centered design approach to electronic health record (EHR) development and usability testing there have been usability and safety risks with EHR technology. Four EHR vendors were asked to provide written descriptions of their usability practices, and we reviewed these descriptions to identify areas where there has been advancement and areas for improvement. All 4 vendors described user-centered design processes and usability testing methods that demonstrate advancement from previous studies of vendor practices. Importantly, vendors are also beginning to address aspects of EHR implementation that play a critical role in shaping EHR usability. There are important areas for improvement in vendor practices including a greater focus on safety and on measurement and benchmarking. Vendors sharing their current usability practices demonstrates a step toward greater transparency which has typically been lacking.